CULTURAL TOURISM – AS ONE OF THE MECHANISMS FOR THE REVIVAL OF THE GREAT SILK ROAD - Rizakhojayeva G. A.,; Baltabayeva A. Yu., (Scientific Journal of Pedagogy and Economics, 2021)
The study is devoted to the study of the form of the emergence of trade architecture of the cities of the Great Silk Road and their impact on the expansion of modern tourism in the region. Сaravanserais, trading cities (markets) of Kazakhstan, Kyrgyzstan and Uzbekistan are outlined as examples. The analysis of the types of planning structure and the situation that divulged the attributes of the trade architecture of the Great Silk Road. In the process of research, a measure of saturation with cultural and historical means of the Great Silk Road regions was deliberated. And also reviewed modern projects for the improvement of this trade and geographical interrelation of cultures of the East and West. The extent of the Great Silk Road was 12 thousand kilometers, so few traders proceeded all the way along the Silk Road. Essentially, they tried to travel in shifts and trade-off goods somewhere halfway. Throughout the Great Silk Road in the cities and villages through which caravans elapsed, there were caravanserais (inns). They had hujras (“lounges”) for merchants and caravan staff, rooms for camels, horses, mules and donkeys, and needed fodder and facilities. Caravanserais were a place where it was attainable to sell and buy in bulk goods interesting to a merchant, and most importantly, to get hold of the latest commercial news and, above all, prices for goods.